Anxiety sensitivity and catastrophizing: Associations with pain and somatization in non-clinical children - Tsao, Jennie C. I. (2009)
This study examined the relationships among anxiety sensitivity (AS), catastrophizing, somatization, and pain in 240 non-clinical children (121 girls; mean age = 12.7 years). Children with pain problems (n = 81; 33.8%) reported greater AS and catastrophizing (p’s < .01) relative to children without pain problems. AS but not catastrophizing was significantly associated with current pain. However, both AS and catastrophizing were significantly associated with somatization. AS and catastrophizing represent related but partially distinct cognitive constructs that may be targeted by interventions aimed at alleviating pain and somatization in children.